Appendix: State by State Detailed Reports (Journal of The Colloquium for Information Systems Security Education, 2016)
The editors of this volume have aggregated data reflecting the CAEs and cyber-readiness of each state in order to serve as a guide for those implementing this and similar local projects. CISSE, as the publisher of this information, is embracing local preparedness as an expansion of the services they can provide its membership of over 200 academic institutions.